Character Strengths and Psychological Wellbeing among Students of Teacher Education - Josep Gustems; Caterina Calderon (International Journal of Educational Psychology, 2014)
The relation between character strengths and psychological well-being can have an important effect on students’ academic performance. We examined relationships between character strengths and psychological well-being as assessed by the Values in Action Inventory of Strengths and Brief Symptom Inventory. A sample of 98 teacher education students participated. The participants showed high scores in character strength scales. The five character strengths with the highest scores were kindness, fairness, teamwork, love, and honesty. The participants scored higher in character strengths that focused on other people than in the strengths that focused on the self, and higher on the so-called “strengths of the heart” than on “strengths of the head”. In our study, the character strengths most closely associated with well-being were love, humour, fairness, honesty, curiosity, and self-regulation. In conclusion, the character strengths are positively related to university students’ psychological well-being.